Effects of Rotation with Trap Crops on Striga (Striga hermonthica Del. Benth) Incidence, its Seed Bank and Sorghum Growth and Yield (University of Khartoum Journal of Agricultural Sciences, 2023)
A trial was conducted for three consecutive seasons (2006/07,2007/08 and 2008/09) in a field artificially infested by Striga hermonthicain the Experimental Farm of the Faculty of Agriculture, University ofSinnar. The effects of a two seasons’ crop rotation on striga incidence, itsseed bank and growth and yield of subsequent sorghum crop wereinvestigated. The rotation comprised the trap crops, cowpea (Vignaunguiculata), millet (Pennisetum glaucum), sesame (Sesamum indicum),sunflower (Helianthus annuus) and fallows, in assorted combinations. Asorghum monoculture, for the three seasons, was included as a control.All treatments reduced striga emergence significantly in comparison tosorghum monoculture. Sunflower and sesame grown for two consecutiveseasons caused the maximum reductions (80%), while a fallow followedby sorghum resulted in the least reduction (42%). Significant reduction instriga capsules (37%) was caused by two consecutive sesame crops. In thesecond season, all treatments significantly reduced striga seed bank,. Twoconsecutive fallows and two consecutive crops each of cowpea, millet andsunflower resulted in the highest reductions in striga incidence (80% -92%), while a fallow followed by sorghum exhibited the least reduction(51-65%). None of the treatments had adverse effects on sorghum standearly in the season; however, at harvest significant reduction wasobserved. Sorghum monoculture resulted in the lowest stand, whilesunflower planted subsequent to a fallow and two successive sunflowercrops affected the highest stands. Among all treatments, sorghum